2012
DOI: 10.1074/jbc.m111.338426
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in 3′-Untranslated Region Contributes to the Regulation of Toll-like Receptor 4 Translation

Abstract: Background: Genetic variation of SNP rs11536889 in 3Ј-UTR of TLR4 is implicated in certain diseases, including periodontitis, gastric atrophy, and prostate cancer. Results: The G allele of rs11536889 inhibited translation, but not transcription, of TLR4. Conclusion: Genetic variation of rs11536889 regulates TLR4 expression. Significance: Polymorphism in rs11536889 could be an excellent genetic marker for the diseases caused by TLR4-ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…SNP rs11536889 is located in the 3'-untranslated region of TLR4, where a genetic change can influence the translation of TLR4 mRNA. Sato et al (2012) showed that rs11536889 can contribute to the regulation of TLR4 translation. They found that peripheral blood mononuclear cells from subjects carrying the C allele secreted higher levels of IL-8 than the cells from subjects with the wild-type genotype.…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs11536889 is located in the 3'-untranslated region of TLR4, where a genetic change can influence the translation of TLR4 mRNA. Sato et al (2012) showed that rs11536889 can contribute to the regulation of TLR4 translation. They found that peripheral blood mononuclear cells from subjects carrying the C allele secreted higher levels of IL-8 than the cells from subjects with the wild-type genotype.…”
Section: Discussionmentioning
confidence: 99%
“…HGF were grown to confluence in 100-mm tissue culture dishes. The media were then changed to DMEM containing 1% FCS for 12 h, and HGF were incubated in this media with or without IL-1β (1 ng/mL) and TNF-α (10 ng/mL) for 24 h, as previously described (16)(17)(18). Total RNA was isolated from triplicate cultures and analyzed for expressions of miRNAs and U6 snRNA by real-time PCR, as described below.…”
Section: Cell Culturementioning
confidence: 99%
“…The cells were cultured at 37°C in 5% CO 2 / 95% air in DMEM containing 10% FCS. They were grown to confluence in 100-mm tissue culture dishes, and the medium was then changed to DMEM containing 1% FCS for 12 h, followed by incubation in this medium with or without IL-1β (1 ng/mL), IL-6 (1 ng/mL), and TNF-α (10 ng/mL) for 24 h as described previously (13)(14)(15)(16)(17)(18)(19). Total RNA was isolated from quadruplicate cultures and analyzed for the expression of AMTN and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA by real-time PCR as described below.…”
Section: Cell Culturementioning
confidence: 99%